Economic evaluation of plerixafor addition in the mobilization and leukapheresis of hematopoietic stem cells for autologous transplantation: a systematic review. (2nd January 2023) - Mesquita Augusto Passos, Roselene; Feldens, Tallys Kalynka; Marcolino, Miriam Allein Zago; Gouvêa, Aline Sampaio; Dos Santos Oliveira, Lais; Menardi Nasser, Luisa; Rodrigues, Roseli Fernandes; de Lourdes Martins Perobelli, Leila; Campolina, Alessandro Gonçalves; de Almeida Neto, Cesar
ABSTRACT: Introduction: Although plerixafor in association with granulocyte colony-stimulating factor (G-CSF) can improve mobilization and collection of hematopoietic stem cells (HSC) by leukapheresis, cost may limit its clinical application. The present study systematically reviews economic evaluations of plerixafor plus G-CSF usage compared to G-CSF alone and compares different strategies of plerixafor utilization in multiple myeloma and lymphoma patients eligible for autologous HSC transplantation. Areas covered: Relevant economic evaluations, partial or complete, were searched on PubMed, Embase, LILACS, and Cochrane Central Register of Controlled Trials for a period ending 30 June 2021. This systematic review was reported following the PRISMA Statement. Six economic evaluations were included, considering the use of upfront or just-in-time plerixafor compared to G-CSF alone or other plerixafor strategies. Most comparisons showed both increased cost and health benefits with the addition of plerixafor. Most analyses favored just-in-time plerixafor compared to upfront plerixafor, with a probable preference for broader cutoffs for just-in-time plerixafor initiation. Expert opinion: Plerixafor is a potentially cost-effective technology in the mobilization of HSC in patients with multiple myeloma and lymphomas eligible for autologous HSC transplantation. There is a decreased number of leukapheresis sessions and remobilizations and a higher yield of CD34+ cells.